PENERAPAN METODE WEIGHTED PRODUCT MODEL UNTUK SELEKSI CALON KARYAWAN - Sri Lestari (Universitas Sriwijaya, 2013)
Abstrak The development company is highly influenced by the performance of human resources, so that each company will try to get qualified employees. Constraints are typically faced by companies is the difficulty of selecting candidates who match the criteria, because the number of the incoming beam, so the possible occurrence of lack of proper decision-making, it certainly should not be allowed to drag on because it will affect the productivity of the company. A selection process of employees with the right candidate to be an important thing, because this process will be obtained from prospective employees who fit the criteria desired by the company. Application of the method is widely used to help solve the problem of selection candidates, one of the methods applied is the Weighted Product Model (WPM), because this method can solve the problems of multi-dimensional and one dimensional. It also produces rankings that can be used as a reference for decision- making right. Application of selection methods in the case of WPM candidates have weaknesses when used to assess a prospective employee this is due to the absence of minimum thresholds as a condition of graduation requirements. Kata kunci: WPM, Employee Selection